The Effect of Reputation, Facilities, and Price Risk on Consumer Decisions to Use Vehicle Repair Services - Yulia Sari; Kartika Sari Lubis (International Journal of Islamic Business and Management Review, 2025)
The automotive industry in Indonesia is becoming increasingly competitive, particularly in after-sales services such as vehicle body repair. This study aims to analyze the impact of Reputation, facilities, and price on consumer decisions when choosing body repair services at PT. Astra International Daihatsu Tbk. Using a descriptive survey method, data was collected from consumers who had used the body repair services at the official workshop. The findings show that both Reputation and facilities significantly influence consumer decisions, although price remains the dominant factor. The majority of consumers feel that the price charged is not aligned with the quality of service received, and the facilities provided by the workshop are still considered inadequate. However, Reputation is acknowledged by a small portion of consumers, indicating the need for improvements in brand image and service quality. This study suggests that PT. Astra Daihatsu should improve its service facilities and pricing to remain competitive, as well as enhance the workshop’s reputation to increase consumer satisfaction and loyalty.